THE BUSINESS PROCESS IMPROVEMENT OF PRODUCTION SCHEDULE AND DAILY SCHEDULE ADHERENCE BY DESIGNING INTEGRATED SYSTEM IN THE DIE CUT AREA AT PT.DEF - I Gusti Putu Ngurah Agung Wahyudi Arta; Johan Krisnanto Runtuk (JIE Scientific Journal on Research and Application of Industrial System, 2022)
PT. DEF is a company that engage in developing children toys. At this time, PT. DEF is trying to implement industrial 4.0 concept. All of the aspects need to implement automation system, especially in the die cut area. In order to assign the job order from customer, the schedule was prepared manually and lack of parameter considerations. Consequently, planner should revise the schedule because they did miscalculation that will impact on job order distribution and unscheduled die cut part. Starting from January 2021 – September 2021 there are 420 die cut part numbers should be assigned to the die cut machine. Since the schedule is prepare manually, PT. DEF experience loss and it reached IDR 236,376,000,00. Thus, integrating the production planner schedule and daily schedule adherence (DSA) should be conducted and followed by user requirements consideration. This research uses business process improvement as the development method. New integrated system that developed using visual basic for application (VBA) can reduce the manual activities and human error issues. By reducing manual activities, according to measurement of cycle time, the new system can operate 102.46 minutes faster than previous system which is 123.58 minutes. It also can reduce 100% unscheduled part every month in the die cut area at PT. DEF. Overall, the saving cost of new integrated system when calculated based on time reduction and unscheduled part number is Rp 10,667,211.93 per month or equal to Rp 128,006,543.14 per year.